Potential of olive oil tourism in promoting local quality food products: A case study of the region of Extremadura, Spain - José Antonio Folgado-Fernández; Ana María Campón-Cerro; José Manuel Hernández-Mogollón (Heliyon, 2019)
This work aims to highlight tourism based on gastronomy, heritage and olive oil-related activities. These activities enhance the knowledge about the product itself and its links with culture and local traditions. Olive oil tourism is based on a typical gastronomic product of internationally recognised quality. This type of tourism boosts sustainable destinations capable of introducing and promoting the consumption of local products. In addition, it favours the implementation of different activities in rural settings, such as routes through the olive groves, gastronomic markets, educational initiatives, historical events, etc. This study analyses the development of olive oil tourism in the district of La Serena in Extremadura (Spain). The study involved 208 tourists that were asked about their experience on oil tourism during their trip. The results emphasize the great potential of development that olive oil tourism can achieve in rural settings as sustainable destinations. From the results obtained, managers of rural settings with a great olive oil tradition can base their tourism strategies on the gastronomic and cultural context of this local product.